Laboratory investigations of mineral dust near-backscattering depolarization ratios. (July 2016) - Järvinen, E.; Kemppinen, O.; Nousiainen, T.; Kociok, T.; Möhler, O.; Leisner, T.; Schnaiter, M.
Abstract: Recently, there has been increasing interest to derive the fractions of fine- and coarse-mode dust particles from polarization lidar measurements. For this, assumptions of the backscattering properties of the complex dust particles have to be made either by using empirical data or particle models. Laboratory measurements of dust backscattering properties are important to validate the assumptions made in the lidar retrievals and to estimate their uncertainties. Here, we present laboratory measurements of linear and circular near-backscattering (178°) depolarization ratios of over 200 dust samples measured at 488 and 552 nm wavelengths. The measured linear depolarization ratios ranged from 0.03 to 0.36 and were strongly dependent on the particle size. The strongest size-dependence was observed for fine-mode particles as their depolarization ratios increased almost linearly with particle median diameter from 0.03 to 0.3, whereas the coarse-mode particle depolarization values stayed rather constant with a mean linear depolarization ratio of 0.27. The depolarization ratios were found to be insensitive to the dust source region or thin coating of the particles or to changes in relative humidity. We compared the measurements with results of three different scattering models. With certain assumptions for model particle shape, all the models were capable of correctly describing the size-dependence of the measured dust particle, albeit the model particles significantly differed in composition, shape and degree of complexity. Our results show potential for distinguishing the dust fine- and coarse-mode distributions based on their depolarization properties and, thus, can serve the lidar community as an empirical reference.